Principles of Universal Design on the Example of Assistive Devices for Specific Groups of Invalids - E. Dryukova, A. (International Journal of Engineering and Technology, 2018)
The present paper considers an auxiliary device for the safe movement ofÂ  visually impaired population in an urban environment, which is based on the use of acoustic and tactile sensations for orientation in space.Â Â